PENGARUH GAYA KEPEMIMPINAN SITUASIONAL, DISIPLIN KERJA DAN KOMUNIKASI EFEKTIF TERHADAP KINERJA PEGAWAI PADA BADAN PENANGGULANGAN BENCANA DAERAH BULELENG - Sudarnaya, I Ketut; Marda Diani, Luh Sista (Komunitas Manajemen Kompetitif, 2024)
The purpose of this study was to determine the influence of situational leadership style, work discipline and effective communication on employee performance at the Regional Disaster Management Agency of Buleleng Regency. The sample in this study amounted to 77 people. Data collection in this study used questionnaire and documentation techniques. The analytical techniques used in this study are validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test tests, f-test tests. The results showed that the results of hypothesis 1 testing showed a positive regression coefficient so that it was concluded that situational leadership style had a positive and significant effect on employee performance. The results of hypothesis 2 testing show a positive regression coefficient so that it is concluded that work discipline has a positive and significant effect on employee performance. The results of hypothesis 3 testing show a positive regression coefficient so that it is concluded that effective communication has a positive and significant effect on employee performance.